2021
DOI: 10.5808/gi.21062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking of bioactive compounds derived from Moringa oleifera with p53 protein in the apoptosis pathway of oral squamous cell carcinoma

Abstract: Moringa oleifera is nowadays raising as the most preferred medicinal plant, as every part of the moringa plant has potential bioactive compounds which can be used as herbal medicines. Some bioactive compounds of M. oleifera possess potential anti-cancer properties which interact with the apoptosis protein p53 in cancer cell lines of oral squamous cell carcinoma. This research work focuses on the interaction among the selected bioactive compounds derived from M. oleifera with targeted apoptosis protein p53 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…This is in line with other previous research such as pelargonidin (PG, a natural food dye) with p53 complex showed the interaction of PG at Arg126, Cys127 and Cys151 (Dey et al, 2021). While one of selected bioactive compounds derived from Moringa oleifera such as Quercetin has the best docking score towards p53 (-6.72) with 3 H-bonding that consists of two bonds with Ile21 and one bond with Glu89 (Rath et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with other previous research such as pelargonidin (PG, a natural food dye) with p53 complex showed the interaction of PG at Arg126, Cys127 and Cys151 (Dey et al, 2021). While one of selected bioactive compounds derived from Moringa oleifera such as Quercetin has the best docking score towards p53 (-6.72) with 3 H-bonding that consists of two bonds with Ile21 and one bond with Glu89 (Rath et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The structure of a protein is predicted with BIOVIA Discovery Studio 2021 predicts the active sites present in the structure of protein, which was utilized for docking. From all synthesized compounds, more potent anticancer compound 17 c and 19 b bioactive compounds were selected which possess good anti‐cancer property based on literature review [29,30,35] …”
Section: Methodsmentioning
confidence: 99%
“…From all synthesized compounds, more potent anticancer compound 17 c and 19 b bioactive compounds were selected which possess good anti-cancer property based on literature review. [29,30,35]…”
Section: Protein Model 2d Structure and Prediction Of Active Sitementioning
confidence: 99%
“…Mo has a fairly high micronutrient and natural bioactive compounds, including phenolic, flavonoids, tannins, alkaloids, saponins, and steroid [9]. Some studies reported that bioactive compounds from Mo may interact with OSCC cell lines and have anti-cancer action by inhibiting cell proliferation [10][11][12]. However, most of them are hydrophilic which is soluble in water, but have low absorption due to poor permeability to cross the lipid membranes of the cells, and have large molecular size resulting in lower bioavailability and therapeutic efficacy [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that bioactive compounds from Mo may interact with OSCC cell lines and have anti-cancer action by inhibiting cell proliferation [10][11][12]. However, most of them are hydrophilic which is soluble in water, but have low absorption due to poor permeability to cross the lipid membranes of the cells, and have large molecular size resulting in lower bioavailability and therapeutic efficacy [7][8][9][10][11][12][13]. Hence, nanotechnology is found to be promising anti-cancer agents as they could reduce the required dose, enhance the action of plant extracts with minimal side effects and enhance the biological activity, and in combination might gain a better therapeutic potential of herbal medicine.…”
Section: Introductionmentioning
confidence: 99%